Design and Simulation of Passive Micromixer in Microfluidic Device - Nizar, Alif Ashraf; Abdul Hamid, Intan Sue Liana (Evolution in Electrical and Electronic Engineering, 2021)
Microfluidic device can be used in numerous fields as its capabilities in fluid mixing on Lab-On-Chips (LOC). The usual mixture between two liquids is to use a passive micro-mixer straight channel. This method is able to mix between the two liquids but for an existing design, a straight channel micro mixer takes time for micro-mixing diffusion. The main purpose of this project is to design passive micromixer and simulate the design in order to analyse the mixing rate. In this paper, three different passive micromixers were evaluated based on the patterns of Y-shaped micromixer. The micromixers are basic straight micromixer, grooved micromixer, and repetitive meandering micromixer. The simulation of micromixer designs were mainly done and analysed in COMSOL Multiphysics, a widely used modelling and simulation software for microfluidic devices. The simulation fluids diffusion in micromixers was determined by the results of concentration’s standard deviation values along the mixing channel width and length of 100μm and 2000μm respectively. The evaluation data of designs comparison shows that repetitive meandering micromixer design was proven as the best model as it attained complete mixed fluids amongst other micromixer designs as it achieved the standard deviation value of 0 faster than other designs.